Field test and cost analysis of four harvesting options for herbaceous biomass handling - Brownell, Douglas; Liu, Jude (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: The nature of most biomass materials is a low bulk density as compared to traditional fuel sources. ?High handling cost could be a limiting factor in utilizing biomass feedstock. ?Understanding available harvesting machinery systems and associated costs is critical to future implementation.? Four popular harvesting machinery systems were studied and costs were analyzed based on field measurements and calculations. ?These four systems included (1) round baling and round bale handling systems, (2) large square baling and square bale handling systems, (3) forage harvester and trucking systems, and (4) large square baling plus square bale compression systems. ?Results indicated that a self-loading forage wagon can reduce the cost to harvest a crop but requires more harvest time.? Large square bales were found to reduce cost of handling and transport as compared to round bales.? Further research is needed to determine storage costs and deterioration loss of the two bale types.? Compressed square bales were found to reduce storage, handling and transport costs.? Compressed bale machinery has a high initial cost, which currently makes only valuable for hay export. Keywords: harvesting machinery system, herbaceous biomass, field, cost DOI: 10.3965/j.issn.1934-6344.2011.03.058-068 ? Citation: Douglas Brownell, Jude Liu. ?Field test and cost analysis of four harvesting options for herbaceous biomass handling. ?Int J Agric & Biol Eng, 2011; 4(3): 58